METASTATIC THYROID CANCERS TREATED AT RANGPUR. - Abu TAHER, Muhammad (The ASEAN Journal of Radiology, 2023)
Thyroid cancer can appear as metastatic disease involving skeletal system as depicted in the two patients treated by surgery, radioiodine ablation and thyroxine at Rangpur.